Da'wah Rhetoric in Public Speaking Activities from Tubagus Wahyudi's Perspective - Huda, Chairul; Azis, Akbar Maulana Abdul (International Journal of Educational Research Excellence (IJERE), 2025)
Communication is essential for all humans, especially as social beings, as it fosters happy lives, welfare, and family harmony. Public speaking is a crucial skill, particularly for students, as it plays a significant role in education through presentations and idea expression. This skill is also vital for future leaders. The research aims to address public speaking challenges based on Tubagus Wahyudi's insights and to share his theories on communication with students and the broader audience. Utilizing qualitative research with a case study approach, the study investigates the impact of Wahyudi's theories on students' communication, particularly in public speaking. Findings indicate that students who engaged with Wahyudi's teachings experienced notable improvements in their communication and socialization skills with peers, family, and the community. Those trained by Wahyudi have become effective presenters and educators, ready to embrace public speaking opportunities spontaneously. This reflects a psychological transformation in individuals learning communication under his guidance. Students express gratitude and satisfaction for having a mentor like Wahyudi, whose methods significantly enhance their communication abilities. The success of his teaching has sparked enthusiasm among students, leading to a growing interest in his courses. Overall, Wahyudi's influence on learning communication and public speaking has led to substantial positive changes in students' lives, motivating them to seek further knowledge and skills in this area.